Women Living their Old Age Autonomously: New Readings from Life Courses and Historical Injustices - Castillo Delgado, Alondra (Revista Chilena de Fonoaudiología, 2022)
This essay is the product of a reflection on the autonomy of women in their old age, and their contributions to the field of health. From stories gathered during a doctoral study regarding their health care, personal reflections emerge that provide new theoretical constructs and challenge the hegemonic proposals related to this matter, thus generating knowledge that is situated and decolonizing, which in turn allows perceiving old age differently. Two central ideas derive from this process: first, it is important to understand the semantic distance between autonomy and independence, where autonomy is built as a decision about oneself and not as the ability to perform the actions that mobilize those decisions; therefore, being autonomous and being independent are parallel and complementary paths that contribute to healthy aging. Secondly, embodying autonomy is an experience that is historically constructed and changes as women age and abandon the obligation to take care of others, centering themselves in their own lives. This does not erase the fact that ageism could threaten their experience. It is proposed to resemanticize these concepts in the context of health and to incorporate a critical and reflexive perspective into health care practices that acknowledges the life courses and the multiple discriminatory systems that undermine the trajectories of women in their old age, to contribute to the construction of a more just and equitable society.